Seroprevalence of SARS-CoV2 in IBD patients treated with biologic therapy - Berte, Roberto; Mazza, Stefano; Stefanucci, Marta Rachele; Noviello, Daniele; Costa, Stefania; Ciafardini, Clorinda; Mileti, Erika; Mapelli, Marina; Pasqualato, Sebastiano; Pinto, Sergio; Favale, Agnese; Vecchi, Maurizio; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: A similar course of COVID-19 in patients with inflammatory bowel diseases [IBD] and in the general population has been reported. However, disease prevalence in IBD patients is presently unknown. In this prospective observational study, we aimed at determining SARS-CoV2 infection prevalence in IBD patients treated with biologic therapy. Methods: From IBD patients under biologic therapy and recruited from three different locations in Italy and Germany, 354 sera were evaluated for antibody presence by RBD ELISA. Control groups were: i] age-matched healthy subjects tested in the same time period in Milan, Italy; ii] healthy subjects collected in the pre-COVID era; iii] IBD patients under biologic therapy collected in the pre-COVID era. Results: Eight out of 354 patients tested positive for the anti-RBD-SARS-CoV2 IgG antibody [prevalence 2.3%]. The percentage of IgG-positive patients among those recruited from Milan was significantly higher than among those recruited from other locations [prevalence 5.4% vs 0.4%, p<0.005]. IgG-positive patients reported a significantly higher incidence of fever, anosmia, and ageusia, and were more likely to have entered into close contact with COVID-19-positive subjects before the study enrolment. Conclusions: Seroprevalence of SARS-CoV2 in IBD patients treated with biologic therapy reflects values measured in the local general population. Specific symptoms and contact history with SARS-CoV2-infected individuals strongly increase the likelihood of SARS-CoV2 seropositivity.
CRIS-Team Scopus Importer:2021-06-04
Keywords: anti-SARS-CoV2 antibodies; COVID-19; IBD; seroconversion